Ultrasonic Welding of Aluminum Alloys to Fiber Reinforced Polymers1. Issue 9 (17th June 2013) - Wagner, Guntram; Balle, Frank; Eifler, Dietmar
<x xml:space="preserve">Abstract</x> To realize multi‐material structures, e.g., out of light metals and fiber reinforced polymer (FRP) composites suitable joining methods are required. The ultrasonic metal welding technology was applied to produce high strength joints between different aluminum alloys and carbon fiber reinforced polymers (CFRPs) in the framework of research unit 524 of the German Research Foundation. The bonding mechanisms were characterized by light optical and scanning electron microscopy (SEM). The performed analysis have shown a bonding zone with an intensive contact between the metallic surface and the load bearing carbon fibers of the CFRP as a result of the ultrasonic welding process. Using precipitation hardening aluminum alloy AA2024 tensile shear strengths of up to 58 MPa could be achieved. In comparison to established joining techniques ultrasonic metal welding can be an interesting alternative to realize dissimilar joints for the automotive or aircraft industry.